Analisis Continuous Wavelet Transform (CWT) Anomali Residual Medan Gravitasi Di Situs Geologi Karangsambung Kebumen Jawa Tengah - Wahyu Hidayat; Wrego Seno Giamboro (Jurnal Mineral, Energi dan Lingkungan, 2018)
Gravity method is a passive geophysical method that provides information on the distribution of rock density below the surface. The gravity method has a weakness at the level of ambiguity in determining the depth of the anomaly. This study aims to determine the depth of the anomaly using Continuous Wavelet Transform (CWT) analysis to overcome the value of ambiguity, so that the results obtained have a high degree of accuracy. The research method is data survey / acquisition and data analysis. This research was conducted in Karangsambung Kebumen, Central Java with the acquisition of gravitational data as many as 56 measurement points. The results of data acquisition then analyzed included reading to mGal, tool height correction, drift, tides, latitude, free air correction, Bouguer correction, and field correction. The results of this correction obtained Complete Bouguer Anomalies (ABL) values which were then reduced to flat fields and regional-residual anomaly filters. The next step is CWT analysis by making incisions on residual anomaly maps. The results showed that the source of the anomaly was between ± 39.2 - 122.9 meters.